CORRELATION OF TRANSIENT ELASTOGRAPHY WITH LIVER IRON CONCENTRATION, AND SERUM FERRITIN LEVELS IN PATIENTS WITH TRANSFUSION-DEPENDENT THALASSEMIA MAJOR PATIENTS FROM OMAN - Khan, Hammad; Panjwani, Vinodh; Al Rahbi, Sara; Eltigani , Abubakr; Qureshi, Rizwan; Unnisa, Khaleeq; Sehar, Najmus; Mittal, Alok; Pathare, Anil (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Aims: In a cross-sectional study we aimed to assess the correlation between ultrasound transient elastography (TE), serum ferritin (SF), liver iron content (LIC) by magnetic resonance imaging (MRI) T2* along with the fibrosis-4 (FIB-4) score as a screening tool to detect significant liver fibrosis among chronically transfusion-dependent beta-thalassemia (TDT) patients. Methods: The study was conducted at a tertiary health center treating TDT patients. Transient elastography was performed within 3 months of Liver MRI T2* examinations at the radiology department. T-test for independent data or Mann-Whitney U test was used to analyze differences between groups and Spearman correlation with linear regression analysis were used to evaluate the correlation between TE liver stiffness measurements and Liver MRI T2* values along with SF levels. Results: In this study on 91 patients, the median age (IQR) of the subjects was 33 (9) years and body mass index was 23.8 (6.1) kg/m2. Median (IQR) TE by fibroscan, MRI T2*(3T), Liver iron concentration (LIC) by MRI Liver T2* and SF levels were 6.38 (2.6) kPa, 32.4 (18) milliseconds, 7(9) g/dry wt., and 1881 (2969) ng/mL, respectively. TE measurements correlated with LIC g/dry wt. (rS =0.39, p=0.0001) and with SF level (rS =0.43, P=0.001) but not with MRI T2* values (rS =-0.24; P=0.98). Conclusion: We observed that in transfusion dependent β thalassemia major patients there was a significant correlation with the TE measured by ultrasound transient elastography, and LIC by MRI as well as SF levels but not with the fibrosis-4 (FIB-4) score. Key Words: Serum ferritin; Fibrosis-4; Transfusion-dependent beta-thalassemia; Transient elastography; Magnetic resonance imaging